2015
DOI: 10.1210/jc.2014-3127
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and Adipose Tissue Signatures in Adults With Prader-Willi Syndrome: A Model of Extreme Adiposity

Abstract: Matched for FM, PWS subjects have a better metabolic profile, a phenotype that could be linked to changes in scAT remodeling and promotion of adipocyte growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 42 publications
1
47
0
2
Order By: Relevance
“…PWS individuals may be less likely to develop T2DM than non-syndromic subjects with comparable obesity. In fact, the lower fasting insulin and HOMA-IR were shown in not only PWS children but also PWS adults 5,6) . However, recent study suggested further investigation with hyperinsulinemic-euglycemic clamp due to failure to reprove this identification 7) .…”
Section: Altered Glucose Metabolism In Pwsmentioning
confidence: 93%
“…PWS individuals may be less likely to develop T2DM than non-syndromic subjects with comparable obesity. In fact, the lower fasting insulin and HOMA-IR were shown in not only PWS children but also PWS adults 5,6) . However, recent study suggested further investigation with hyperinsulinemic-euglycemic clamp due to failure to reprove this identification 7) .…”
Section: Altered Glucose Metabolism In Pwsmentioning
confidence: 93%
“…Ainsi, un profil normal de méthylation de la région 15q11-q12 exclut à 99 % le diagnostic de syndrome de Prader-Willi. [6]. Le traitement par l'hormone de croissance permet de restaurer, au moins partiellement, certaines propriétés du tissu adipeux, avec chez l'enfant, une normalisation du nombre de précurseurs adipocytaires.…”
Section: Diagnosticunclassified
“…La publication par la Haute autorité de santé du programme national de diagnostic et de soins 6 en 2012, a permis de décrire la prise en charge multidisciplinaire dans le centre de référence et les centres de compé-tence qui sont répartis sur le territoire, en relation avec le médecin traitant. En 2011, le plan Obésité a labellisé deux établissements de soins de suite et de réadaptation pour enfants (un en Île-de-France et un près de Toulouse), en lien avec les sites des centres de référence, pour l'accueil des enfants atteints de SPW et d'autres obésités syndromiques ou apparentées.…”
Section: La Prise En Charge Une Organisation Des Soins Et Un Maillageunclassified
“…The development of AT occurs early in PWS infants before the onset of weight gain 25) , so PWS can be seen as an exceptional model of early and massive AT development, notably in subcutaneous depots 7) . The mechanisms of reduced LBM in PWS patients are not fully understood.…”
Section: Adipose Tissue In Prader-willi Syndromementioning
confidence: 99%
“…However, obesity remains a critical problem in PWS teenagers and adults because it leads to severe complications, such as sleep disorder, cardiac or respiratory failure, and physical disability 6) . Obesity status also plays on a crucial role in development of metabolic syndrome (Mets) in PWS children and adults [7][8][9][10] . Several studies focused on the metabolic outcomes of PWS adults.…”
mentioning
confidence: 99%